Association Between the Extent of Periodontal Inflammation and the Severity of Rheumatoid Arthritis in Japanese Patients With Rheumatoid Arthritis - Hiroko Hashimoto; Shimpei Hashimoto; Yoshihiro Shimazaki (Elsevier, 2021)
Objective: Periodontal inflammation can affect the progression of rheumatoid arthritis (RA), and RA drugs may influence the periodontal condition of patients with RA. We examined whether the association between periodontal inflammation and the severity of RA is influenced by RA medication. Methods: This cross-sectional study recruited 98 Japanese patients with RA from an orthopaedic clinic. We assessed the severity of RA using the Steinbrocker class and stage. The periodontal inflamed surface area (PISA) was used as an indicator of periodontal status. We obtained data on RA medications from medical records. We examined the associations among periodontal tissue inflammation, RA medications, and RA severity using multinomial logistic regression analyses. Results: In univariate multinomial logistic regression analyses, no significant association between PISA score and RA severity was observed. There was no significant association between PISA score and RA severity in multivariate analyses not including variables about RA drugs as independent variables. However, in multivariate analyses adjusted for RA drugs and other confounding variables, patients with a PISA >550 mm2 had significantly higher odds ratios (ORs) for Steinbrocker class III-IV and stage III-IV (OR, 20.24; 95% confidence interval [CI], 1.78-229.85 and OR, 12.42; 95% CI, 1.79-86.49, respectively) compared to patients with PISA score ≤550 mm2. Conclusion: The extent of periodontal inflammation is associated with the severity of RA independent of RA medications.